Comparative analysis of salivary antimicrobial resistance genes in dental students: A PCR and questionnaire study. - Marwan Mansoor Mohammed; Priyadharshini Sekar; Jahida Al Jamal; Lujayn Abu Taha; Asma Bachir; Sausan Al Kawas (PLoS ONE)
Introduction Antimicrobial resistance (AMR) is a major global healthcare challenge, with limited treatment options due to the decline in new antibiotics. The human oral cavity, home to diverse bacteria, is crucial for maintaining oral and systemic health. Recent studies suggest that saliva may serve as a reservoir for AMR genes. However, there is a lack of research on this topic in the UAE and most Middle Eastern countries. This study investigated the presence of AMR genes in saliva from forty 5th-year dental students and forty 1st-year dental students. Materials & methods Demographic and health information was collected via a 28-question structured questionnaire. Real-Time PCR was used to detect a panel of preselected AMR genes in bacterial DNA from saliva samples. Results Participants' ages ranged from 20 to 31 years, with 41 females and 39 males. The prevalence of AMR genes varied: blaCTX-M grp 1 (29%), blaCTX-M grp 9 (85%), blaCTX-M grp 8 (39%), blaOXA-48 (69%), blaKPC-1 (6%), blaVIM (49%), DHA (53%), ACC (25%), MOX (59%), armA (83%), and rmtB (63%). There were no significant differences in AMR gene prevalence between 5th-year and 1st-year students or between male and female students. Conclusion The study revealed a high occurrence of AMR genes in the oral microbiome. Comprehensive metagenomic analysis is recommended to further evaluate the prevalence and relative abundance of these genes in the UAE population. Establishing a database for these ARGs could aid in effective future monitoring.